Preparing Preservice Teachers’ Minds, Hearts and Actions for Teaching in Remote Indigenous Contexts - Osborne, Barry (The Australian Journal of Indigenous Education, 2003)
ABSTRACT This paper examines some challenges we confront working with preservice teachers prior to serving in remote Indigenous communities. Some challenges include what preservice teachers bring to their studies - subjectivities, experiential understandings of teaching and notions of childhood/adolescence, culture and social justice, all of which involve minds, emotions and our notions of our places in society. Some challenges involve linking new notions of teaching to what they already know which may entail unlearning before relearning. Some challenges involve making sense of the theory/action dialectic - teasing out links between strongly held but unarticulated values, beliefs and actions that derive from them. Some challenges involve anticipating what it might be like to live and teach in a remote setting and preparing to work effectively across cultures. I then discuss how we might tackle them in the light of productive pedagogy and culturally relevant pedagogy (Osborne, 2001a, 2001b).